Physical activity level and mobility of hip, pelvic and spine in sagittal plane during forward bending - Zawadka, Magdalena; Gawda, Piotr; Skublewska-Paszkowska, Maria; Smołka, Jakub; Łukasik, Edyta (Journal of Education, Health and Sport, 2017)
Introduction and purpose Forward bending is a part of standard evaluation of spine mobility during physical examination. More sedentary lifestyle seems to be a factor lead to limited range of motion. However influence of physical activity level on kinematics of joints during bending has not been previously investigated. In this study, kinematics of the hip joint, pelvic and the lumbar spine during forward bending were examined using the three-dimensional motion analysis. Material and method Participants were included to one of two groups: I-higher physical activity level, II-lower physical activity level on the basis of their leisure time physical activity. Participants performed forward bending with straight knees. Results Minimal value of pelvic angle reached during motion was higher in I group than in II group (p=0.043).Second group demonstrated larger spine range of motion than the first group (p=0.021). Conclusions This results may indicate a limited motor control and core stability associated with lower level of physical activity. Causes of different spino-pelvic motion need further investigations.